Change Management: an Empirical Study on Managing Employee Resistance to Organizational Change - Andi Ibbar; Steviani Batti (International Forum of Researchers and Lecturers, 2025)
Employee resistance remains one of the most significant barriers to successful organisational change implementation. Despite extensive theoretical frameworks, organizations continue to struggle with change initiatives, with failure rates ranging from 60-70%. His study investigates the key factors contributing to employee resistance during organizational change and evaluates the effectiveness of various management strategies in overcoming such resistance. A mixed-methods approach was employed, combining quantitative surveys (n=450) from employees across 15 organizations undergoing major changes and qualitative interviews (n=35) with change management leaders. Data collection occurred over 12 months during active change implementation periods. The study identified five primary resistance factors: fear of job security (78%), lack of communication (65%), insufficient training (58%), past negative experiences (52%), and loss of autonomy (47%). Organizations employing comprehensive communication strategies, participative change approaches, and structured training programs showed 40% higher success rates in change implementation. Effective resistance management requires a multi-faceted approach combining proactive communication, employee participation, skill development, and emotional support. Organizations that address resistance systematically achieve significantly better change outcomes.